Preparation method of ultra-fine grain high-entropy carbide-based metal ceramic
Through high-energy ball milling-presintering process and phenolic resin coating technology, the problems of coarse grains and excessive oxygen content of high entropy metal cermet materials were solved, and ultrafine grain high-entropy carbide-based metal cermet with high mechanical properties were obtained.
Patent Information
- Application Number
- CN202411751941.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing high-entropy cermet materials have poor mechanical properties due to coarse grains, and are prone to introduce uneven oxygen content and carbon distribution during the preparation process.
Using a high-energy ball milling-presintering process, ultrafine grain high-energy carbide powder or micron-scale high-energy carbide powder is mixed with phenolic resin and ceramic milling balls, high-energy ball milling and presintering treatment is performed, and then ball milling with metal powder and spray granulation and pressing is performed. Finally, ultrafine grain high-energy carbide-based metal cermet is obtained by vacuum or atmosphere pressure sintering.
The lattice defects and oxygen content in the powder are effectively eliminated, the carbon distribution is controlled, and high-entropy carbide ceramics with complete grain structure and small particle size are obtained, which significantly improves its mechanical properties, such as bending strength and fracture toughness.
Smart Images

Figure CN119506679A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal ceramics, and in particular to a method for preparing ultrafine grain high entropy carbide-based metal ceramics. Background Art
[0002] High entropy carbide is a ceramic material composed of 4-5 transition metal carbides with equal (nearly equal) molar metal atomic ratios, such as (TiWMoVNb)C, (TaZrNbWMo)C, etc. It has become a potential candidate material for the new generation of metal ceramics due to its excellent chemical stability, high red hardness, and wear resistance. At present, high entropy carbide ceramic powder is prepared by solid phase reaction method, and its sintering temperature is high, and the powder particle size is coarse, which reduces the mechanical properties of metal ceramics. Based on this, it is of good application value to develop a metal ceramic with fine grains and high entropy carbide ceramic phase.
[0003] However, there are currently two main methods for preparing high-entropy metal ceramics. The first is to directly mix multi-component carbide powder and metal powder evenly, and then sinter them at high temperature liquid phase to form single-phase high-entropy carbide ceramic grains from multi-component carbides through a dissolution-precipitation mechanism. However, this method requires a higher sintering temperature to ensure that the carbides of each component react fully and form high-entropy carbide ceramics, which will lead to grain growth and the formation of intergranular pores, reducing the mechanical properties of metal ceramics. The second method is to pre-synthesize high-entropy carbide ceramic powder, and then directly mix the high-entropy carbide ceramic powder with a metal binder phase (iron, cobalt, nickel), and then sinter them through a conventional process to obtain a high-entropy metal ceramic with uniform structure and controllable phase. However, due to the coarseness of the synthesized carbide powder, this method is difficult to obtain high-performance metal ceramic materials with fine grains.
[0004] To this end, in order to obtain high-entropy carbide-based metal ceramics with fine grains, there are currently two methods that can be easily thought of. The first method is to use ultrafine high-entropy ceramic powder as raw material, but this method is often a chemical synthesis method, such as co-precipitation method, high-entropy ceramic precursor synthesis method, which has low production efficiency and high cost, and is difficult to industrialize and mass produce. The second method is to fully crush and refine the multi-component carbide ceramic powder to form an ultrafine mixed powder; or directly grind and crush the multi-component carbide ceramic powder and metal powder. After the powder is activated, the sintering activity is high, and a high-entropy carbide-based metal ceramic material with fine grains can be obtained. However, this method is prone to introduce excessive oxygen content during high-energy ball milling, and the method requires thorough reduction and consumption of carbon content at a higher temperature to absorb oxygen, which will lead to closed pores inside the metal ceramic; at the same time, in order to make up for the lack of carbon, additional carbon black needs to be added to the metal ceramic, but it is difficult to achieve micron-level uniformity through mixing.
[0005] Therefore, the high entropy metal ceramics in the prior art have technical problems such as poor mechanical properties due to coarse grains. Ultrafine high entropy carbide ceramic powders can be prepared by mechanical crushing or chemical synthesis, but the following problems are still difficult to solve.
[0006] The mechanical crushing method is a commonly used technology in industrial production, but high-energy ball milling is required to grind micron-sized high-entropy carbide ceramic powders or multi-component carbide powders (4-5 carbide powders) to tens to hundreds of nanometers. The ball milling process is likely to cause many lattice defects on the powder surface, resulting in difficulty in controlling the sintering structure, excessive adsorption of oxygen by the powder, and difficulty in eliminating it in the subsequent sintering process. Excessive oxygen content will consume the total carbon of the metal ceramic, and there is a problem of uneven carbon content distribution by mixing carbon supplementation. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the prior art and propose a method for preparing ultrafine grain high entropy carbide-based cermets. The method has low cost, can be industrialized, and effectively solves the problem of uneven distribution of adsorbed oxygen and carbon supplementation during the crushing process.
[0008] In order to achieve the above object, a method for preparing an ultrafine grain high entropy carbide-based cermet comprises the following steps: Step 1, dispersing multi-component carbide powder or micron-sized high entropy carbide powder in an organic solvent, adding 1-5wt% of phenolic resin, and then adding ceramic grinding balls, the ball-to-material ratio is 10-25:1, the ball particle size is 0.2-1.0 mm, the ball milling time is 24-60h, and the ball milling speed is 100-300r / min; Step 2: pre-sintering the high-entropy ceramic powder after high-energy ball milling and drying, the pre-sintering atmosphere is argon gas, the purity of which is better than 99.999%, the pre-sintering temperature is 1300-1500°C, and the holding time is 1-5h; Step 3: conventionally ball mill the high entropy carbide ceramic powder obtained above and the metal powder, add 1-3wt% paraffin or rubber forming agent, use anhydrous ethanol as the ball milling medium, use carbide balls, the ball-to-material ratio is 5-8:1, and the ball milling time is 24-60h; then spray granulate the mixture, and the particle size of the powder after granulation is 20-100μm; Step 4, pressing the granulated powder into a shape at a pressing pressure of 50-200 MPa; Step 5, the green sheet is degreased and sintered to obtain an ultrafine-grained high-entropy carbide-based cermet; the sintering is vacuum sintering or atmosphere pressure sintering, and if vacuum sintering is performed, the vacuum degree is 5-50Pa; if it is atmosphere pressure sintering, the protective gas is argon, and the gas pressure is 0.5-5MPa; the sintering temperature is 1400-1500°C, and the sintering time is 1-3h.
[0009] Preferably, in step 1, the organic solvent is anhydrous ethanol, acetone, etc.
[0010] Preferably, in step 1, the ceramic grinding balls are alumina grinding balls or zirconia grinding balls.
[0011] Preferably, in step 1, the amount of phenolic resin added is 2-4wt%.
[0012] Preferably, in step 1, the ball ratio is 15-20:1, the ball milling time is 30-48h, the ball milling speed is 150-200r / min, and then the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored.
[0013] Preferably, in step 2, the pre-sintering temperature is preferably 1350-1400° C., and the holding time is 2-3 h. After this step, the particle size of the obtained high entropy carbide ceramic powder is 100-300 nm, and the powder oxygen content is ≤0.8wt%.
[0014] Preferably, in step three, the ball milling time is 30-48h.
[0015] Preferably, in step three, the particle size of the granulated powder is 30-50 μm.
[0016] Preferably, in step five, the degreasing temperature is 300-500° C., and the degreasing time is 2-5 hours.
[0017] Preferably, in step 1, the carbide is commercial carbide powder, and the micron-sized high entropy carbide powder is micron-sized high entropy carbide powder synthesized by conventional solid phase reaction, wherein each type of carbide is composed of at least 4 of TiC, WC, Mo2C, TaC, NbC, ZrC, VC and HfC in transition metal carbides. In order to maintain the high entropy system, the molar ratio of the metal elements of each added phase is similar, and the difference in the ratio of each metal element is ≤10wt%. The metal bonding phase used is at least one of iron, cobalt and nickel, and the metal phase content is 15-25wt%.
[0018] Preferably, in step 1, the transition metal carbide contains at least two phases, TiC and WC.
[0019] Preferably, in step 1, the average particle size of the commercial carbide powder is 0.5-5.0 microns, if high entropy carbide powder is used, its particle size is 5-10 microns, and the average particle size of the binder phase powder is 1.0-3.0 microns.
[0020] The present invention adopts a high-energy ball milling-pre-sintering process to eliminate the lattice defects of micro-nano high entropy carbide powder and the oxygen content adsorbed in the powder; high-energy ball milling is to obtain nano-scale high entropy carbide ceramic powder by ball milling micron-scale high entropy carbide ceramic powder or multiple carbide powders; and the pre-sintering process is to pre-sinter the nano-scale powder to 1300-1500°C in a protective atmosphere, allowing atoms to diffuse through defects to eliminate intracrystalline defects, and the adsorbed oxygen can react with the carbon on the surface of the powder to be eliminated. By uniformly mixing and coating the high-carbon content phenolic resin on the surface of the high-entropy carbide ceramic powder, it is evenly dispersed, and the total carbon content in the metal ceramic can be better controlled.
[0021] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention adopts a chemical mixing method, that is, dissolving a phenolic resin with a high carbon content in an organic solvent, and mixing and coating it with a high entropy carbide ceramic powder. After drying, the surface of the high entropy carbide ceramic powder has a uniform distribution of phenolic resin; compared with the traditional mixing by adding carbon black to supplement carbon, its dispersion uniformity is better.
[0022] 2. The present invention adopts a high-energy ball milling-pre-sintering process to obtain a high-entropy carbide ceramic powder with a complete grain structure and a grain size of 100-300nm. The oxygen content of the powder is ≤0.8wt%, and it has good sintering activity and organization.
[0023] 3. The present invention can obtain a bending strength better than 2300 MPa and a fracture toughness better than 9.5 MPa·m 0.5 Ultrafine-grained high-entropy carbide-based cermet materials with a Rockwell hardness better than 92.0 HRA can be widely used in bearing materials, cutting tools, mold materials and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0025] Figure 1 The present invention is a flow chart of a method for preparing ultrafine-grained high-entropy carbide-based cermet.
[0026] Figure 2The transmission electron microscopic morphology of the high entropy carbide ceramic powder after high energy ball milling and the high entropy carbide ceramic powder after pre-sintering at 1350°C in Example 1 of the present invention. (a) and (c) are high entropy carbide ceramic powders after high energy ball milling, and there are many defects in their lattices; while (b) and (d) are high entropy carbide ceramic powders after pre-sintering at 1350°C, and their grain surfaces are curved and the lattice structure is complete.
[0027] Figure 3 This is the microscopic morphology of the ultrafine-grained high-entropy carbide-based cermet in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0029] like Figure 1-Figure 3 As shown, the composition is: 85(Ti,W, Ta,Nb, Mo)C-15Ni metal ceramic, wherein the atomic ratio of Ti:W:Ta:Nb:Mo is 1.0:1:1.1:0.9:1.0.
[0030] The mass fraction of the metal ceramic component is 85 parts of high entropy carbide ceramic powder and 15 parts of a bonding phase, wherein the average particle size of the high entropy carbide powder is 5.0 microns, and the particle size of the nickel powder is 1.0 microns.
[0031] The preparation steps of the high entropy carbide-based metal ceramic are as follows: (1) dispersing multi-component carbide powder or micron-sized high entropy carbide powder in anhydrous ethanol, adding 2wt% phenolic resin, and then adding alumina ceramic grinding balls, the ball-to-material ratio is 15:1, the ball particle size is 0.5 mm, the ball milling time is 30h, and the ball milling speed is 150r / min; then the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored. (2) The high entropy ceramic powder after high-energy ball milling and drying is pre-sintered, the pre-sintering atmosphere is argon, the pre-sintering temperature is 1350℃, and the insulation time is 2h. (3) The high entropy carbide ceramic powder obtained above is conventionally ball milled with metal powder, 2wt% paraffin forming agent is added, the ball milling medium is anhydrous ethanol, carbide balls are used, the ball-to-material ratio is 5:1, and the ball milling time is 48h; then the mixture is spray granulated, and the particle size of the powder after granulation is 30μm. (4) The granulated powder is pressed into a shape at a pressing pressure of 80 MPa. (5) The pressed green body is degreased and sintered to obtain an ultrafine-grained high-entropy carbide-based cermet; the sintering is vacuum sintering with a vacuum degree of 10 Pa; the sintering temperature is 1450°C and the sintering time is 1 hour. The degreasing temperature is 400°C and the degreasing time is 2 hours.
[0032] After the above steps, the particle size of the high entropy carbide ceramic powder obtained by the high energy ball milling-pre-sintering method is 120nm, and the oxygen content of the powder is 0.8wt%. After sintering, the size of the high entropy carbide ceramic grains is 0.6 microns, its porosity is A04B00C00 level, the material flexural strength is 2450MPa, and the fracture toughness is 9.8 MPa·m 0.5 , Rockwell hardness is 92.5HRA, and it is a metal ceramic tooling material with wide application potential.
[0033] like Figure 1 As shown, composition: 80(W, Mo,Ti, V, Nb)C-20Co metal ceramic, where the atomic ratio of W: Mo:Ti:V:Nb = 1:0.9:1.0:1.0:0.9.
[0034] The mass fraction of the metal ceramic component is 80 parts of high entropy carbide ceramic powder and 20 parts of metal bonding phase. The high entropy carbide powder is added in the form of single carbide powder, including WC, Mo2C, TiC, VC, and NbC. The average particle sizes of the above powders are 2.5, 3.0, 1.8, 2.5, and 1.6 microns, respectively, and the particle size of the cobalt powder is 2.5 microns.
[0035] The preparation steps of the high entropy carbide-based metal ceramic are as follows: (1) dispersing multi-component carbide powder in anhydrous ethanol, adding 3wt% phenolic resin, and then adding zirconium oxide ceramic grinding balls, the ball-to-material ratio is 20:1, the ball particle size is 0.8mm, the ball milling time is 36h, and the ball milling speed is 180r / min; then the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored. (2) The high entropy ceramic powder after high-energy ball milling and drying is pre-sintered, the pre-sintering atmosphere is argon, the pre-sintering temperature is 1400℃, and the insulation time is 1h. (3) The high entropy carbide ceramic powder obtained above is conventionally ball milled with metal powder, 3wt% rubber forming agent is added, the ball milling medium is anhydrous ethanol, carbide balls are used, the ball-to-material ratio is 6:1, and the ball milling time is 35h; then the mixture is spray granulated, and the particle size of the powder after granulation is 50μm. (4) The granulated powder is pressed into a shape at a pressing pressure of 150 MPa. (5) The pressed green body is degreased and sintered to obtain an ultrafine grained high entropy carbide-based cermet; the sintering is atmosphere pressure sintering, the inert gas is argon, the gas pressure is 2 MPa; the sintering temperature is 1480°C, and the sintering time is 1 hour. The degreasing temperature is 450°C, and the degreasing time is 2 hours.
[0036] After the above steps, the particle size of the high entropy carbide ceramic powder obtained by the high energy ball milling-pre-sintering method is 200nm, and the oxygen content of the powder is 0.6wt%. After sintering, the size of the high entropy carbide ceramic grains is 0.8 microns, its porosity is A04B00C00 level, the material flexural strength is 2320MPa, and the fracture toughness is 10.2 MPa·m 0.5 , Rockwell hardness is 92.2 HRA, and it is a metal ceramic tooling material with wide application potential.
[0037] like Figure 1 As shown, composition: 75(Ti,W, Nb, V, Zr)C-10Fe-15Ni metal ceramic, where the atomic ratio of Ti:W:Nb:V:Zr = 1:1.0:1.0:1.0:1.0.
[0038] The mass fraction of the metal ceramic component is 75 parts of high entropy carbide ceramic powder and 15 parts of a binder phase, wherein the average particle size of the high entropy carbide powder is 8.0 microns, the particle size of the iron powder is 2.0 microns, and the particle size of the nickel powder is 3.0 microns.
[0039] The preparation steps of the high entropy carbide-based metal ceramic are as follows: (1) dispersing micron-sized high entropy carbide powder in acetone, adding 3wt% phenolic resin, and then adding alumina ceramic grinding balls, the ball-to-material ratio is 20:1, the ball particle size is 0.8mm, the ball milling time is 48h, and the ball milling speed is 180r / min; then the powder after high-energy grinding is vacuum dried, and after drying, it is vacuum packaged and stored. (2) The high entropy ceramic powder after high-energy ball milling and drying is pre-sintered, the pre-sintering atmosphere is argon, the pre-sintering temperature is 1350℃, and the insulation time is 1h. (3) The high entropy carbide ceramic powder obtained above is conventionally ball milled with metal powder, 2wt% paraffin forming agent is added, the ball milling medium is anhydrous ethanol, carbide balls are used, the ball-to-material ratio is 8:1, and the ball milling time is 30h; then the mixture is spray granulated, and the particle size of the powder after granulation is 50μm. (4) The granulated powder is pressed into a shape at a pressing pressure of 100 MPa. (5) The pressed green body is degreased and sintered to obtain an ultrafine-grained high-entropy carbide-based cermet; the sintering is vacuum sintering with a vacuum degree of 10 Pa; the sintering temperature is 1500°C and the sintering time is 2 hours. The degreasing temperature is 400°C and the degreasing time is 2 hours.
[0040] After the above steps, the particle size of the high entropy carbide ceramic powder obtained by the high energy ball milling-pre-sintering method is 250nm, and the oxygen content of the powder is 0.6wt%. After sintering, the size of the high entropy carbide ceramic grains is 0.8 microns, its porosity is A04B00C00 level, the material flexural strength is 2280MPa, and the fracture toughness is 10.5 MPa·m 0.5 , Rockwell hardness is 92.2 HRA, and it is a metal ceramic tooling material with wide application potential.
[0041] Comparative Example 1 Other conditions are the same as those in Example 1, except that the added high entropy ceramic powder is directly mixed with the metal binder after high-energy ball milling without going through step 2, pre-sintering.
[0042] The particle size of the high entropy carbide ceramic powder obtained by high-energy ball milling is 60nm, and the oxygen content of the powder is 3.2wt%. After sintering, the size of the high entropy carbide ceramic grains is 1.5 microns, its porosity is A08B02C00 level, the material flexural strength is 2050MPa, and the fracture toughness is 8.2 MPa·m 0.5 , Rockwell hardness is 91.3 HRA, which is difficult to meet the industrial demand for tooling products.
[0043] Comparative Example 2 The other conditions were the same as those in Example 2, except that phenolic resin was not added to the organic solvent, but 1.8 wt % pyrolytic carbon black (the residual carbon content of the phenolic resin was -60%) was directly added.
[0044] The particle size of the high entropy carbide ceramic powder obtained by the high-energy ball milling-pre-sintering method is 200nm, and the oxygen content of the powder is 1.2wt%. After sintering, the size of the high entropy carbide ceramic grain is 1.0 micron, its porosity is A08B00C00 level, the material flexural strength is 2140MPa, and the fracture toughness is 9.2 MPa·m 0.5 , Rockwell hardness is 91.2HRA, which is difficult to meet the industrial demand for tooling products.
[0045] Comparative Example 3 The other conditions are the same as those in Example 3, except that the atomic ratio of Ti:W:Nb:V:Zr is 1:0.7:1.0:1.0:0.9.
[0046] The particle size of the high entropy carbide ceramic powder obtained by the high-energy ball milling-pre-sintering method is 230nm, and the oxygen content of the powder is 0.8wt%. After sintering, the size of the high entropy carbide ceramic grains is 0.9 microns, its porosity is A06B00C00 level, the material flexural strength is 2180MPa, and the fracture toughness is 8.2 MPa·m 0.5 , Rockwell hardness is 92.5HRA, which is difficult to meet the industrial demand for tooling products.
[0047] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for preparing an ultrafine grain high entropy carbide-based cermet, characterized in that: The steps include: Step 1, dispersing multi-component carbide powder or micron-sized high entropy carbide powder in an organic solvent, adding 1-5wt% of phenolic resin, and then adding ceramic grinding balls, the ball-to-material ratio is 10-25:1, the ball particle size is 0.2-1.0 mm, the ball milling time is 24-60h, and the ball milling speed is 100-300r / min; Step 2: pre-sintering the high-entropy ceramic powder after high-energy ball milling and drying, the pre-sintering atmosphere is argon gas, the purity of which is better than 99.999%, the pre-sintering temperature is 1300-1500°C, and the holding time is 1-5h; Step 3: conventionally ball mill the high entropy carbide ceramic powder obtained above and the metal powder, add 1-3wt% paraffin or rubber forming agent, use anhydrous ethanol as the ball milling medium, use carbide balls, the ball-to-material ratio is 5-8:1, and the ball milling time is 24-60h; then spray granulate the mixture, and the particle size of the powder after granulation is 20-100μm; Step 4, pressing the granulated powder into a shape at a pressing pressure of 50-200 MPa; Step 5, the green compact is degreased and sintered to obtain an ultrafine grain high entropy carbide-based cermet; the sintering is vacuum sintering or atmosphere pressure sintering, the vacuum degree of the vacuum sintering is 5-50Pa, and the protective gas of the atmosphere pressure sintering is argon gas with a gas pressure of 0.5-5MPa; The sintering temperature is 1400-1500°C and the sintering time is 1-3h.
2. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step 1, the carbide is commercial carbide powder, and the micron-sized high entropy carbide powder is micron-sized high entropy carbide powder synthesized by conventional solid phase reaction; wherein each type of carbide is composed of at least 4 of TiC, WC, Mo2C, TaC, NbC, ZrC, VC and HfC among transition metal carbides; the difference in the ratio of each metal element is ≤10wt%; the metal bonding phase used is at least one of iron, cobalt and nickel, and the metal phase content is 15-25wt%.
3. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 2, characterized in that: The transition metal carbide contains at least two phases, TiC and WC.
4. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 2, characterized in that: The average particle size of the commercial carbide powder is 0.5-5.0 microns. If high entropy carbide powder is used, its particle size is 5-10 microns. The average particle size of the binder phase powder is 1.0-3.0 microns.
5. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step 1, the ceramic grinding balls are alumina grinding balls or zirconia grinding balls, the ball ratio is 15-20:1, the ball milling time is 30-48h, and the ball milling speed is 150-200r / min.
6. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step 1, the organic solvent is anhydrous ethanol, acetone, etc.
7. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step 1, the amount of phenolic resin added is 2-4wt%.
8. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step 2, the pre-sintering temperature is preferably 1350-1400° C., and the holding time is 2-3 hours.
9. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step three, the ball milling time is 30-48 hours, and the particle size of the granulated powder is 30-50 μm.
10. The method for preparing an ultrafine grain high entropy carbide-based cermet according to claim 1, characterized in that: In step five, the degreasing temperature is 300-500° C., and the degreasing time is 2-5 hours.
Citation Information
Patent Citations
High-entropy hard alloy and preparation method thereof
CN117737541A
High-entropy carbonitride ceramic in-situ reinforced WC-based hard alloy and preparation method thereof
CN118422028A
(TaNbTiZrHf) C-SiC composite material and preparation method thereof
CN118546001A
Silicon carbide ceramic
GB1478898A
Nanostructured carbide cermet powders by high energy ball milling
US6793875B1
Cited By
High-entropy carbide composite ceramic as well as preparation method and application thereof
CN121362912A
Preparation method of plate-shaped crystal tungsten carbide in-situ reinforced metal ceramic tool and mold and metal ceramic tool and mold material
CN122256746A